Analysis of Factors Affecting Land and Building Tax Revenue in Takalar District - Hamzah, Linduaji; Samsinar; Azis, Muhammad (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aims to determine how big the independent variables are, in this case the area of the building, the tax notice payable (SPPT) and the classification of tax objects simultaneously and partially and to analyze the most dominant variables on the level of land and building tax revenue in Takalar district as measured by based on NJOP, the population in this study is the Takalar Regency Regional Revenue Agency, while the sample used is PBB Tax Realization Data 2018-2022, building area data, tax return number data and tax object classification data using multiple liner regression analysis techniques using collection techniques documentation data whose data source comes from the regional revenue agency of Takalar Regency.The results of this research show: Based on the simultaneous test (F), the variable number of building areas (X1), the variable number of tax notices owed (X2) and the number of tax object classifications (X3) have a calculated F value of 42,590 and an F table value of 4.757 where 42,590 > 4.757, which means that variables X1, based on the partial test (t) of the variable total building area (X1) H0 is rejected and H1 is accepted because the calculated t value is > from t table where the calculated t on variable significant to variable y. based on the partial test (t) the variable tax notice payable (x2) h0 is accepted and h1 is rejected because the calculated t value < from t table where the calculated t on variable has a significant effect on the variable Y. based on the Partial Test (t) Tax object classification variable (X3) H0 is accepted and H1 is rejected because the calculated t value is < from t table where the calculated t on variable X3 is -0.805 and the t table is 2.446, where - 0.805 < 2.446, thus variable